Dacarbazine-Loaded Targeted Polymeric Nanoparticles for Enhancing Malignant Melanoma Therapy - Xiong, Wei; Guo, Zhengdong; Zeng, Baoyan; Wang, Teng; Zeng, Xiaowei; Cao, Wei; Lian, Daizheng (Frontiers in Bioengineering and Biotechnology, 2022)
Dacarbazine (DTIC) dominates chemotherapy for malignant melanoma (MM). However, the hydrophobicity, photosensitivity, instability, and toxicity to normal cells of DTIC limit its efficacy in treating MM. In the present study, we constructed star-shaped block polymers nanoparticles (NPs) based on Cholic acid -poly(lactide-co-glycolide)-b-polyethylene glycol (CA-PLGA-b-PEG) for DTIC encapsulation and MM targeted therapy. DTIC-loaded CA-PLGA-b-PEG NPs (DTIC-NPs) were employed to increase the drug loading and achieve control release of DTIC, followed by further modified with nucleic acid aptamer AS1411 (DTIC-NPs-Apt), which played an important role for active targeted therapy of MM. In vitro, DTIC-NPs-Apt shown good pH-responsive release and the strongest cytotoxicity to A875 cells compared with DTIC-NPs and free DTIC. In vivo results demonstrated that the versatile DTIC-NPs-Apt can actively target to site of MM and exhibited excellent anti-tumor effects with no obvious side effects. Overall, this research provided a multi-functional NPs, which endow a new option for the treatment of MM.